Adequação de uma planta de não tecidos à produção de produtos de alto desempenho - Almeida, Rodolfo Gutierres Mathias de (Universidade do Vale do Rio dos Sinos, 2014)
This document has like main goal show a Project plan to adapt a nonwoven production facility to supply raw material to a large multinational company of fast consuming goods, which looks for a national partner to develop high performance nonwovens that currently it imports from European market. Such nonwovens will be used like raw material to make baby diapers and feminine care products. On other hand, this potential new customer demands a higher level of quality assurance and process control in comparison with the current national and Latin America costumers. Adapt to its acceptance criteria demands in significant changes in quality / process controls, industrial layout, acquisition of equipments and internal training. The project is aligning with company vision and strategies, which is be recognized like the best option of nonwoven supplying for the global market of hygiene fabrics. The document involves good practices in project management, from the PMBOK, highlighting the management of integration, scope, time, cost, quality, human resources, risks and acquisitions.
Keywords: Plano de gerenciamento do projeto; Escopo do projeto; Desenvolvimento de novos clientes chave; Estratégia de mercado; Project management plan; Project Scope; Key costumers development; Market strategies